Artificial aquifer recarge experiments in the Portuguese Campina de Faro Case-study area - Diamantino, C. (2007)
This paper presents the preliminary results of the experimental work developed in Portugal in the framework of the 6th Framework Programme GABARDINE Project, Groundwater artificial recharge based on alternative sources of water: Advanced integrated technologies and management, as well as in the framework of a PhD Thesis under development at LNEC. The case study area is located in the Southern Portuguese Algarve region, more precisely in Campina de Faro, near the city of Faro. The case study area is approximately 9 km2 large, being located in a section of the aquifer system of Campina de Faro. This aquifer system was declared as a vulnerable zone concerning the EU nitrates Directive. So, the aquifer needs groundwater rehabilitation, to fulfil the Water Framework Directive goals. The artificial recharge experiments intend to facilitate the accomplishment of those goals. Therefore, one of the main objectives of the research is the optimisation of groundwater rehabilitation based on artificial recharge aiming the minimization of diffuse pollution effects caused by typical local agricultural practices.